Utilization of collaborative learning models in elementary schools - sulfira, sri; paputungan, frezy (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
The collaborative learning model is a learning process carried out collectively in groups with different perspectives, relying on one another to achieve predetermined learning objectives. The focus is on the students being researched in the learning process. How is the implementation of the collaborative learning model in the subject of Physical Education and Health (PJOK) at SD NEGERI 7 BULANGO SELATAN? What are the implications of the collaborative learning model on students' engagement and cooperation in the subject of PJOK during the mid-semester examination process? The aim of this research is to understand the implementation of the collaborative learning model to identify the implications of the collaborative learning model on students' activity and cooperation in PJOK, specifically in floor exercise material. This research employs a qualitative approach utilizing quiz applications. Data collection techniques include observation, interviews, and documentation. Analysis data